Penilaian Kinerja Keuangan Perusahaan melalui Analisis Likuiditas dan Profitabilitas pada PT Indofood Sukses Makmur Tbk Tahun 2021–2023 - Tomi Irianto; Amran Manurung (YASIN, 2026)
The importance of financial performance analysis has become increasingly prominent in the face of competitive business rivalry, especially in food and beverage sector companies, because financial performance is the main indicator in assessing a company’s ability to manage resources and maintain business sustainability. This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk based on liquidity ratios and profitability ratios during the 2021–2023 period. This study used a descriptive method with a quantitative approach. The data used were secondary data from the company’s annual financial statements obtained through the official website of the Indonesia Stock Exchange (IDX). The analysis was conducted using financial ratios, including the Current Ratio and Quick Ratio as liquidity indicators, as well as Return on Assets (ROA) and Return on Equity (ROE) as profitability indicators. The results showed that the financial performance of PT Indofood Sukses Makmur Tbk from the liquidity aspect was still below industry standards, so the company’s ability to meet short-term obligations was not yet optimal. From the profitability aspect, ROA showed a value that was still relatively low compared with industry standards, while ROE showed fairly good performance because the company was able to generate profit from its equity. This study concludes that, in general, the company’s financial performance still needs to be improved, especially in asset management to increase its ability to generate profit.